Características biométricas do cafeeiro conilon irrigado associadas a índices fisiológicos e nutricionais de nitrogênio - Busato, Camilo (2015)
Conilon coffee plant demonstrates high productive potential and this is reflected in its high nutritional need, mainly for nitrogen (N), which stands out against the nutrients on account of the high quantity needed and the different functions it performs